Analysis of the correlation between obesity, oro-naso-sensory alterations, inflammatory process and COVID-19: a narrative review (Research, Society and Development, 2022)
Introduction: The acute inflammatory syndrome caused by COVID-19 amplifies the chronic inflammatory process caused by obesity, leading to an even more severe inflammatory cascade, exacerbating the cellular destruction of the different tissues affected by the disease, including the olfactory and gustatory tissues. Objectives: to elucidate and summarize the correlation between obesity, oro-naso-sensory alterations, the inflammatory process and COVID-19. Methodology: This is a narrative review, which used PubMed, Research Gate and Google Scholar databases. Results and discussion: As a direct and indirect consequence of the infection of the goblet cells secreting the nasal mucosa and epithelial cells of the tongue, two of the most striking symptoms are the oro-naso-sensory impairment, which in its most advanced stage can lead to ageusia and /or anosmia, which may only last for the active phase of COVID-19 or last long after the disease resolves. As for anosmia and its relationship to inflammation and obesity, a recent connection has been discovered between apoptosis and inflammation of the olfactory mucosa, where a significant increase in caspase-3 activity is associated with a marked loss of olfactory neurons and their axonal projections. paralleled an increased expression of Iba-1, suggesting an increase in pro-inflammatory cells. Conclusion: Both obesity and SARS-CoV-2 infection lead the body to an inflammatory state that is sometimes acute, sometimes chronic, but in both, uncontrolled. This inflammatory state most often ends up affecting the olfactory and gustatory epithelium, causing an important and sometimes even irreversible impairment of function.